PROSPECTS OF APPLICATION OF ARTIFICIAL INTELLIGENCE IN THE TRAINING AND CONTINUOUS PROFESSIONAL DEVELOPMENT OF PEDIATRICIANS - Volosovets, Oleksandr; Naumenko, Oleksandr; Kucherenko, Inna; Tsymbalyuk, Ruslan; Vygovska, Oksana; Kryvopustov, Sergii; Kramariov, Sergii; Burlaka, Ievgeniia; Khomenko, Viktoria; Kuznetsov, Oleksii (Eastern Ukrainian Medical Journal, 2026)
Introduction. The need to actively integrate AI tools into the daily practice of pediatricians and family physicians has become a pressing priority, with the aim of improving the quality of medical care provided to children.Objective: Based on an analysis of the literature, to summarize the latest achievements regarding the implementation of AI in continuing pediatric education and to identify promising areas for its application.Materials and Methods. A bibliosemantic method was used. Information retrieval and analysis of scientific sources were conducted using the scientometric databases of PubMed (https://pubmed.ncbi.nlm.nih.gov/) for the past 10 years.Results and Discussion. Our analysis of scientific publications about the application of AI in pediatric education for the period from 2015 to 2025 demonstrates a progressive increase in their number, reflecting the current transformation of the educational paradigm in pediatrics.The use of such widely adopted AI tools as DeepSeek and ChatGPT has now become an integral part of modern medical education due to their ability to rapidly process and structure large datasets and information.To enhance pediatricians’ knowledge regarding the use of artificial intelligence models in the diagnosis and treatment of childhood diseases, existing educational programs must be improved to account for the specificities of applying artificial intelligence tools in pediatric practice, as well as the associated challenges and ethical issues. A phased approach to teaching medical students and pediatricians the fundamentals of artificial intelligence throughout their educational and professional careers is recommended. At all stages, artificial intelligence tools should be used only as a supplement to existing educational programs.Conclusions. Artificial intelligence currently serves as a powerful driver of change in the training and professional development of pediatricians, offering tools that make pediatric education more clinically oriented and personalized.